The robust running ape: Unraveling the deep underpinnings of coordinated human running proficiency - Kiely, J. (Frontiers in Psychology, 2017)
In comparison to other mammals, humans are not especially strong, swift or supple. Nevertheless, despite these apparent physical limitations, we are among Natures most superbly well-adapted endurance runners. Paradoxically, however, notwithstanding this evolutionary-bestowed proficiency, running-related injuries, and Overuse syndromes in particular, are widely pervasive. The term `coordination` is similarly ubiquitous within contemporary coaching, conditioning, and rehabilitation cultures. Various theoretical models of coordination exist within the academic literature. However, the specific neural and biological underpinnings of `running coordination,` and the nature of their integration, remain poorly elaborated. Conventionally running is considered a mundane, readily mastered coordination skill. This illusion of coordinative simplicity, however, is founded upon a platform of immense neural and biological complexities. This extensive complexity presents extreme organizational difficulties yet, simultaneously, provides a multiplicity of viable pathways through which the computational and mechanical burden of running can be proficiently dispersed amongst expanded networks of conditioned neural and peripheral tissue collaborators. Learning to adequately harness this available complexity, however, is a painstakingly slowly emerging, practice-driven process, greatly facilitated by innate evolutionary organizing principles serving to constrain otherwise overwhelming complexity to manageable proportions. As we accumulate running experiences persistent plastic remodeling customizes networked neural connectivity and biological tissue properties to best fit our unique neural and architectural idiosyncrasies, and personal histories: thus neural and peripheral tissue plasticity embeds coordination habits. When, however, coordinative processes are compromised—under the integrated influence of fatigue and/or accumulative cycles of injury, overuse, misuse, and disuse—this spectrum of available `choice` dysfunctionally contracts, and our capacity to safely disperse the mechanical `stress` of running progressively diminishes. Now the running work burden falls increasingly on reduced populations of collaborating components. Accordingly our capacity to effectively manage, dissipate and accommodate running-imposed stress diminishes, and vulnerability to Overuse syndromes escalates. Awareness of the deep underpinnings of running coordination enhances conceptual clarity, thereby informing training and rehabilitation insights designed to offset the legacy of excessive or progressively accumulating exposure to running-imposed mechanical stress